Relations Between Student Procrastination and Teaching Styles: Autonomy-Supportive and Controlling - Codina, Nuria; Valenzuela, Rafael; Pestana, Jose V.; Gonzalez-Conde, Joan (Frontiers in Psychology, 2018)
Procrastination is a complex problem that can be defined as delaying an intended course of action (despite anticipating adverse consequences). Even when some students have equivalent motivation and skill levels, they tend to procrastinate more frequently than others. Approaches that analyse whether contextual influences may prevent or promote dysregulation processes associated with procrastination are scarce. According to Self-Determination Theory, contextual influences can facilitate self-regulated motivation (e.g. autonomous pursuit of interests or personal goals), if teaching style is autonomy-supportive and guarantees the satisfaction of students’ basic psychological needs for perceived competence, autonomy and relatedness. Contrariwise, school context can also impede the development of autonomous motivation if teachers frustrate the satisfaction of their students’ psychological needs by recurring to controlling teaching behaviours, such as controlling use of reward , negative conditional regard, excessive personal control, or intimidation. The goal of the present study was to assess the relations between controlling and autonomy-supportive teaching behaviours, psychological needs satisfaction (of the needs for competence, autonomy, and relatedness), and four distinct measures of procrastination: general procrastination, decisional procrastination, procrastination linked to task avoidance and pure procrastination. Data based on public university undergraduate students (N = 672) shows that controlling teaching behaviours are associated negatively with psychological needs satisfaction and positively with procrastination. Contrariwise, autonomy-supportive teaching behaviours are positively associated with psychological needs satisfaction and negatively with procrastination.. The data obtained is useful for suggesting new lines of research to study the link between contextual influences and the prevention of academic procrastination in view of Self-Determination Theory. Also, our results suggest new pedagogical approaches where teachers can create contextual conditions that help to prevent or reduce procrastinating tendencies.